Physicochemical and Functional Properties of Brown Rice (Oryza sativa) and Wheat (Triticum aestivum) Flour and Quality of Composite Biscuit Made Thereof (The Agriculturists, 2012)
The consumer demand is increasing for composite flour based bakery products like biscuits. The incorporation of brown rice flour can be justified in composite flour based biscuits as it has beneficial nutraceutical properties and its gluten-free nature can play important role in preventing celiac problem. The physicochemical and functional properties of brown rice and wheat flour were studied and biscuits were prepared with the incorporation of brown rice flour in 0, 5, 10, 15 and 20 % with the wheat flour to assess the quality and acceptability of the biscuits. The water absorption capacity of brown rice flour was lower than that of wheat flour (p?0.05), whereas oil absorption and foaming capacity of brown rice flour were significantly higher than that of wheat flour (p ?0.05). The brown rice flour had higher least gelation concentration (30.66%) as compared with wheat flour (20.33%). As the concentration of brown rice flour was increased, spread ratio of biscuits decreased. The biscuits containing 5, 10 and 15% brown rice flour indicated that addition of increasing level of brown rice flour had higher ash, fat, moisture and crude fiber contents, while protein and total carbohydrate contents found lower in the biscuits. Statistical analysis of biscuits containing various amount of brown rice flour (0, 5, 10, 15 and 20% brown rice flour) showed that control biscuits (0% brown rice flour) secured the highest score for color, flavor, texture and overall acceptability, which is followed by biscuits containing 10, 5,15 and 20% brown rice flour. DOI: http://dx.doi.org/10.3329/agric.v10i2.13135 The Agriculturists 2012; 10(2) 20-28